AI-POWERED HEALTHCARE DIAGNOSIS - Iosifidi, Eleni; Andriopoulou , Maria-Ioanna (Open Schools Journal for Open Science, 2024)
AI has significantly enhanced the diagnosis of patients in a number of ways. Professionals can receive assistance in evaluating medical pictures, including X-rays, MRIs, and CT scans, through AI-powered diagnostic tools. In addition, by taking into account a variety of patient data, such as genetic data, behavioral features, and medical records, AI can increase the reliability of risk models for forecasting. Furthermore, chatbots or digital assistants powered by artificial intelligence (AI) can collect the patient’s medical information and symptoms in order to make first diagnoses and suggestions.